A compact double-band planar printed slot antenna for sub-6 GHz 5G wireless applications - Ishteyaq, Insha; Shah Masoodi, Issmat; Muzaffar, Khalid (International journal of microwave and wireless technologies, 2021)
A planar rectangular slot antenna with dual-band operation and realized higher peak gain is proposed, designed, and fabricated for sub-6 GHz 5G applications. The antenna possesses a rectangular radiating slot with the inverted stub on its upper edge excited simultaneously by a micro-strip feed line having a double folded T-shaped structure. The fabricated design is of compact size with the radiating portion of 0.3 λ0 × 0.17 λ0 (λ0 represents free-space wavelength) and profile of 0.009 λ0. The measured results show the operating frequency bands of 3.29–3.63 GHz and 4.3–5.2 GHz, with a peak gain of around 7.17 dBi. The higher frequency band is generated by the feed patch and the slot whereas lower resonant frequency band is generated by the stub loaded on the slot. The measured results are in a good agreement with the simulated results. The proposed design is suitable for the International Telecommunications Union sub 6 GHz applications.